Development of a nasal spray containing aminocaproic acid and a copolymer of N-vinylpyrrolidone and 2-methyl-5-vinylpyridine for use in the prevention of influenza and other viral respiratory infections - A. S. Karpova (Тонкие химические технологии)
Objectives. Prevention of influenza and viral respiratory infections is one of the major public health problems today. The aim of the study was to develop the formulation and production conditions for a nasal spray that can be used in the prevention of influenza and other viral respiratory infections, based on aminocaproic acid and a copolymer of N-vinylpyrrolidone and 2-methyl-5-vinylpyridine.Methods. The influence of pH and temperature on the transparency of the copolymer solution was investigated using a turbidimeter to determine the optimal pH for the dosage form. The pH value was determined using a pH meter equipped with a combined glass electrode. The presence or absence of opalescence in the solution was determined visually, whereas the dynamic viscosity of the solution was determined at 25.0±0.5°С using a rotational viscometer. The optimal temperature and mixing speeds were selected as part of the technological development process. Quantitation of the active substances in the resulting drug was conducted using a previously reported high performance liquid chromatography method. A preliminary evaluation of the drug’s shelf life was performed via stability studies using the accelerated aging method.Results. Drug stability was ensured when the pH range of the dosage form was between 5.5 and 6.2. The addition of a thickening agent is not advisable due to undesired interactions between the excipients and the active substances during storage. Ideally, the drug composition for nasal use was aminocaproic acid (1 wt %) and the copolymer (0.5 wt %) in aqueous solution. A phosphate buffer solution with pH 5.5 was selected as the solvent for the dosage form to ensure the stability of the drug solution and ease-of-use without any disruptions in the normal functioning of the cilia in the nasal cavity. The optimal technology for drug production was determined, and the control parameters for this process were highlighted. Drug stability studies conducted via the accelerated aging method revealed that the estimated shelf life of the dosage form was 2 years. Conclusions. A new formulation and optimized production conditions were developed for a drug based on aminocaproic acid and a copolymer of N-vinylpyrrolidone and 2-methyl-5-vinylpyridine, in the form of a nasal spray, for the prevention of influenza and other viral respiratory infections.